CONFLITO RELIGIOSO, MARTÍRIO E EXALTAÇÃO VISIONÁRIA: O CASO DE ESTEVÃO EM ATOS 6,1-8,3 - Hein, Armindo Edegar (2004)
The proposal of this dissertation is to do read the narrative in Acts 6,1 8, 3 in the perspective of an old martyr tradition. The Hellenists started to conflict with the Hebrews, Stephen confront the Jews of the Diaspora assembled in the synagogues, and is brought to the Synadrion and executed. The reason of his execution is his critic concerning the law and the temple. After a vision in form of an ecstatic experience he is violently murdered. Lucas, by this, describes Stephen as a victorious hero. The reality of conflicts, opposition, persecution and martyrdom does not indicate defeat, but the strengthening of faith. The death of Stephen is interpreted within this tradition. The comprehension of the relation between Stephen and the Hellenists is fundamental for the understanding of the continuation of the movement of the followers of Jesus and for the development of the post-eastern Christology.(AU)